Indonesia's Honey Competition Strategy: A New Institutional Economics Analysis - Muhamad Fauzi; Awang Saputra (universitas teuku umar, 2022)
Honey product is one type of product that provides many economic and health benefits so that it is in great demand by all citizens of the world, even animals. There is a gap between production and consumption globally so that every country competes to increase its production not only for domestic needs but also to meet world demand for honey products. There are still many honey producers whom individuals or families manage so that the volume produced is still minimal, either for own consumption or directly sold to consumers. To meet global honey needs, the interests of medium-large companies are essential but still empower honey producers or individual honey farmers. The study aims to maintain its commitment to quality and halalness and corporate analysis strategy following the new institutional economics approach. This study uses descriptive qualitative research using literature studies. The study results found that the company is very committed to product quality assurance and halalness and implementing the company's strategy at level 4 as new institutional economics, namely economic order 3 with resource efficiency, the formation of marginal prices and structures, and business sustainability.